The feasibility, acceptability and clinical impact of a guided self-help mobile intervention (INTERconNEcT-EDs) for individuals with eating disorders: protocol for two multicenter randomized controlled trials - Gianluca Lo Coco; Gaia Albano; Salvatore Gullo; Valentina Cardi; Cristina Segura-Garcia (Journal of Eating Disorders)
Abstract Background Treatments for eating disorders (EDs) are marked by high rates of relapses and can be ineffective for almost one in two people. It has been suggested that digital self-help might enhance treatment engagement, retention and efficacy in this patient group. A novel guided self-help mobile intervention (i.e. INTERconNEcT-EDs) to target psychological distress and eating psychopathology in young adults with ED symptoms has been developed. INTERconNEct-EDs is an online, eight-week, guided self-help (GSH) program based on an integrated approach which combines elements of psychoeducation, behaviour change and interpersonal therapy tailored to individual’s interpersonal difficulties. Methods Two randomized controlled trials (RCTs) will be conducted to examine the acceptability, feasibility and impact of INTERconNEcT-EDs on a range of psychological outcomes of outpatients with eating disorders or people in the community with symptoms of disordered eating, in Italy. In the first RCT, 172 adult outpatients with EDs from two public clinical services will be recruited and randomised to treatment as usual (TAU) alone or TAU plus INTERconNEcT-EDs. The primary outcome will be patient psychological distress. Secondary outcomes will include eating disorder psychopathology, interpersonal distress, quality of life, motivation to adhere to standard treatment and INTERconNEcT-EDs, emotion dysregulation, and patient satisfaction, at end of the eight-week treatment and 3-month follow-up. In the second RCT, 70 adult individuals from the community with symptoms of disordered eating (measured by a self-report) will be randomised to receiving INTERconNEcT-EDs or a waiting list condition. The primary and secondary outcomes are identical to those of the first RCT. Moreover, participant’s service use will be recorded at the end of the eight-week protocol. INTERconNEcT-EDs consists of psychoeducational workbooks, video-clips, weekly themed, and synchronous forum groups facilitated by individuals recovered from an ED. Participants randomised to TAU + INTERconNEcT-EDs in the first trial will also receive weekly online interpersonal group sessions. Group sessions will be tailored to target individual’s interpersonal difficulties, as measured by the Inventory of Interpersonal Problems at baseline. Discussion The results of this study will determine the feasibility and clinical impact of a novel eating disorder transdiagnostic self-help intervention with the potential of broad reach and scalability. Trial registration ClinicalTrials.gov Identifier NCT06551974.